Axial Spondyloarthritis Unresponsive to Secukinumab, an IL-17A Inhibitor Therapy, a Case Report - Gantira Danasasmita; Anna Ariane; Rudy Hidayat (Journal of Clinical Rheumatology and Immunology)
Introduction Axial spondyloarthritis (axSpA) is a group of autoinflammatory disease that hypothetically caused by tumor necrosis factor (TNF) axis and interleukin (IL)-23/IL-17 axis. Based on algorithm of treatment from ASAS/EULAR 2022, biologic agent is indicated if patient did not response to NSAIDs, the first line treatment. TNF inhibitor and IL-17 inhibitor are two biologic agent that has been approved and gave significant result in improving disease activity. Case Description A 47 years old woman who has been diagnosed with axSpA since 2022. At first she was given medication with NSAIDs. She has also been given conventional DMARD, sulfasalazine an methotrexate, until maximum dose but still no response in controlling the disease activity. After about one year of treatment, she finally tried using the biologic agent, Secukinumab. She was given 150 milligram weekly initial dose for a month, followed by monthly administration. After administering the eight dose, she achieved inactive disease activity. However, after the fourteenth dose, symptoms began to reappear and disease activity became very high like the first time of diagnosis. Discussion IL-17A inhibitor (IL-17Ai) has been widely used for treating axSpA since ASAS20/40 and partial response at 16 week was reached 61,36 and 14%. IL-17Ai seem more effective in ameliorating entheseal inflammation and new bone formation, in accordance with role of IL-23/IL-17 axis in stimulating osteoclast. ASAS/EULAR recommend patients who fail therapy with one biological agent in 12 weeks to switch to another type of biological agent. However there’s still no publication data for efficacy to give TNF inhibitor after IL-17Ai or JAK inhibitor failure. Conclusion The effectiveness of biological agents in axSpA is quite similar. In cases where therapy fails, it is still an open question whether the optimal therapy choice is to change the type of drug or a combination of two types of biological agents.